TEENAGERS' EXPERIENCES IN PERCEIVING THEIR BODIES AS A TRIGGER FOR LOW SELF-ESTEEM - Iin Andini Ismail; Yasintha Sari Pratiwi; Rizky Amayana Saputri; Wardah Hafizhah (LP2M IAI Al-Khairat Pamekasan, 2026)
Weight dissatisfaction is a common psychological phenomenon experienced by adolescents and has the potential to affect the development of self-esteem. Social pressure, ideal body standards, and social comparison make adolescents more vulnerable to negative self-evaluations. This study aims to explore in depth the subjective experiences of adolescents experiencing weight dissatisfaction and its impact on self-esteem. This study used a qualitative approach with a phenomenological design and was analyzed using Interpretative Phenomenological Analysis (IPA). Study participants consisted of two adolescents who were purposively selected and met the criteria for experiencing weight dissatisfaction and low self-esteem. Data were collected through in-depth semi-structured interviews. The results revealed three main themes: adolescents' dissatisfaction with their body condition, the impact of body dissatisfaction on self-esteem, and adolescents' efforts to overcome body dissatisfaction, which were broken down into nine superordinate themes. The findings indicate that body dissatisfaction contributes to decreased self-esteem, the emergence of negative emotions, and social avoidance. However, adolescents also demonstrate adaptive coping strategies through social support and self-acceptance processes. This study provides theoretical implications for the phenomenological understanding of body image and practical implications for guidance and counseling services oriented towards self-acceptance and strengthening social support for adolescents.